Buspirone Dose-Response on Facilitating Forelimb Functional Recovery in Cervical Spinal Cord Injured Rats. Issue 1 (26th February 2021) - Ahmed, Rakib Uddin; Edgerton, V. Reggie; Li, Shuai; Zheng, Yong-Ping; Alam, Monzurul
Buspirone, widely used as a neuropsychiatric drug, has also shown potentials for motor function recovery of injured spinal cord. However, the optimum dosages of such treatment remain unclear. In this study, we investigated the dose-response of Buspirone treatment on reaching and grasping function in cervical cord injured rats. Seventeen adult Sprague-Dawley rats were trained to reach and grasp sugar pellets before a C4 bilateral dorsal column crush injury. After 1 week post-injury, the rats were divided into 3 groups to receive 1 of 3 different dosages of Buspirone (i.p., 1 dose/day: 1.5, n = 5; 2.5, n = 6 and 3.5 mg/kg b.w., n = 6). Forelimb reaching and grip strength test were recorded once per week, within 1 hour of Buspirone administration for 11 weeks post-injury. Different dose groups began to exhibit differences in reaching scores from 4 weeks post-injury. From 4-11 weeks post-injury, the reaching scores were highest in the lowest-dose group rats compared to the other 2 dose groups rats. Average grip strength was also found higher in the lowest-dose rats. Our results demonstrate a significant dose-dependence of Buspirone on the recovery of forelimb motor functions after cervical cord injury with the best performance occurring at the lowest dose tested.